Research progress of biomaterials and innovative technologies in urinary tissue engineering - Duan, Liwei; Wang, Zongliang; Fan, Shuang; Wang, Chen; Zhang, Yi (Frontiers in Bioengineering and Biotechnology, 2023)
Substantial interests have been attracted to multiple bioactive and biomimetic biomaterials in recent decades because of their ability in presenting a structural and functional reconstruction of urinary tissues. Some innovative technologies have also been surging in urinary tissue engineering and urological regeneration by providing insights into the physiological behavior of the urinary system. As such, the hierarchical structure and tissue function of the bladder, urethra, and ureter can be reproduced similarly to the native urinary tissues. This review aims to summarize recent advances in functional biomaterials and biomimetic technologies toward urological reconstruction. Various nanofirous biomaterials derived from decellularized natural tissues, synthetic biopolymers, and hybrid scaffolds were developed with desired microstructure, surface chemistry, and mechanical properties. Some growth factors, drugs, as well as inorganic nanomaterials were also utilized to enhance the biological activity and functionality of scaffolds. Notably, it is emphasized that advanced approaches, such as 3D (bio)printing and organoids, have also been developed to facilitate structural and functional regeneration of the urological system. So in this review, we discussed the fabrication strategies, physiochemical properties, and biofunctional modification of regenerative biomaterials and their potential clinical application of fast-evolving technologies. In addition, future prospective and commercial products are further proposed and discussed.